2019
DOI: 10.1039/c9bm01212e
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling peptide-based nanodrug delivery systems

Abstract: The present review outlines the methods designing self-assembling peptide-based NDDs for small molecule drugs, with an emphasis on the different drug delivery strategies and their applications in using peptides and peptide conjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 162 publications
1
38
0
Order By: Relevance
“…This self-assembly peptide-based drug delivery contains amino acids, which contributes beneficial activity to deliver peptides such as biocompatibility, biodegradability, flexible responsiveness, patientspecific therapy, disease-specific therapy, etc. and most of the drug deliveries are formulated as nanoparticles which control biodistribution, enhance efficacy, reduces toxicity 24,25,26 .…”
Section: Peptide-based Drug Delivery Systemmentioning
confidence: 99%
“…This self-assembly peptide-based drug delivery contains amino acids, which contributes beneficial activity to deliver peptides such as biocompatibility, biodegradability, flexible responsiveness, patientspecific therapy, disease-specific therapy, etc. and most of the drug deliveries are formulated as nanoparticles which control biodistribution, enhance efficacy, reduces toxicity 24,25,26 .…”
Section: Peptide-based Drug Delivery Systemmentioning
confidence: 99%
“…The lipopeptides are a class of molecules with one or more lipid chains attached to a short peptide. Recently, self-assembled peptide-based nanomaterials have attracted significant attention, as functional materials [43][44][45][46][47][48][49]. Short peptide-based amphiphiles have been studied as hydrogelators due to their ability to assemble into a large range of novel nanostructures and their rational design for various applications, such as molecular sensors, tissue engineering, and drug-delivery systems [50][51][52][53][54][55][56].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we conjugated short synthetic ELPs (peptides, rather than polypeptides) with short synthetic triple-helical CLP domains and have shown that the association of the CLP triple helix substantially lowers the high inverse T t of the short peptidebased ELP domain into experimentally tractable and, in some cases, physiologically relevant temperature ranges (21,22). Subsequently, we demonstrated the formation of assembled ELP-CLP conjugates by tuning the hydrophobicity of ELP domains comprising (VPGXG) 4 , in which the number of repeats equipped with phenylalanine (F) or tryptophan (W) residues in the X position was varied (23). In contrast to vesicle structures, these W-containing ELP-CLP conjugates formed nanoscale platelet morphologies under aqueous conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure, molecular geometry, and solvent conditions can be tuned to affect the size, shape, and interfacial curvature of peptide-containing assembled structures ( 1 , 2 ), and the development of systematic design rules for the manipulation of architectures via small changes in sequence would offer substantial opportunities to expand their use ( 2 , 3 ). Stimuli-responsive domains have been incorporated that can undergo substantial property changes in response to small external changes in their environment, with triggers such as temperature, pH, and solvent ( 1 , 3 ); thermoresponsiveness is perhaps the most widely used owing to its ease of application ( 4 ), and the fact that peptide conformations such as helix, β turn, and coiled-coils can be manipulated by temperature ( 2 ). Accordingly, stimuli-responsive peptide-amphiphilic copolymers have demonstrated significant promise as drug carriers ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation